Comprehensive Analysis on Heterogeneous Wireless Network in High-Speed Scenarios. (22nd May 2018) - Zhang, Yuyang; Zheng, Tao; Dong, Ping; Luo, Hongbin; Pang, Zhibo
Abstract : Greater demands are being placed on the access bandwidth, stability, and delay of network because of the quickening rhythm of life and work, especially in mobile scenario. In order to obtain a stable network with low latency and high bandwidth in mobile scenario, taking advantage of the wireless heterogeneous network in parallel is a good choice. Nowadays, people are increasingly concerned about the network quality under the mobile scenario. Some scholars have done the relevant measurements. However, all of those measurements mainly investigate part of the network parameters or part of mobile scenarios. In this paper, we make the following contributions. Firstly, in high-speed mobile scenario, the wireless network qualities of different vendors are measured synthetically. Secondly, we analyze the benefits of taking advantage of the different vendors. Thirdly, we deploy the replication link mechanism in high-speed mobile scenario and propose an algorithm to remove the duplicate packet in high-speed mobile scenario. And the algorithm can also be used in another multipath schedule algorithm to improve the reliability.